Electrocardiographic changes present in patients diagnosed with metabolic syndrome (Revista Venezolana de Salud Pública, 2018)
Metabolic syndrome is a disease that currently represents a multiple risk factor for developing cardiovascular disease. This research aimed to determine the electrocardiographic changes present in patients diagnosed with metabolic syndrome (MS).
Keywords: Metabolic syndrome; electrocardiogram; cardiovascular risk